Relationships between otolith and fish size from Mediterranean and north‐eastern Atlantic species to be used in predator–prey studies. Issue 4 (26th August 2016) - Giménez, J.; Manjabacas, A.; Tuset, V. M.; Lombarte, A.
Abstract : Regressions between fish length and otolith size are provided for 40 species from the north‐eastern Atlantic Ocean and 142 species from the Mediterranean Sea. Regressions were also estimated at genus level. Most of the regressions ( c . 84%) explained a high percentage of the deviance (>75%).